Consumer Acceptance in Emerging Towards Using E-Grocery Shopping: A Systematic Literature Review - Rosli, Noor Reenshafirra; Sahudin, Zahariah; Putit, Lennora (Advances in Social Sciences Research Journal, 2024)
Online grocery shopping plays an essential part in today’s online market as it is the most rapidly evolving online shopping category. The main purpose of this paper is to review the increasing number of studies on online grocery adoption in this area. Online groceries are used extensively throughout the world, but they are still relatively new in developing nations like Malaysia. Researchers have studied the use of online groceries extensively, but some factors influence their adoption. We retrieved scholarly articles on online grocery adoption published from 2015-2023 through the Scopus and Web of Science (WoS) database. After the screening process, some papers were excluded due to unmatched criteria. Therefore, 61 previous papers were reviewed concerning the adapted theories, methodology, and findings. Therefore, to close the gap, this study's goal is to give an in-depth review of the factors that influence consumers to adopt online grocery shopping through the Technology Acceptance Model (TAM) as a baseline model. This suggests in the future, e-grocery could be an important market for rapid commerce online shopping services. This paper is built upon a systematic literature review method. The significant result of this research will help online grocery service providers plan and increase customer intention to use their products to develop relevant strategies.